Process Optimization for Ethyl Ester Production in Fixed Bed Reactor Using Calcium Oxide Impregnated Palm Shell Activated Carbon (CaO/PSAC) - A Buasri; B Ksapabutr; M Panapoy; N Chaiyut (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
The continuous production of ethyl ester was studied by using a steady-state fixed bed reactor (FBR). Transesterification of palm stearin (PS) and waste cooking palm oil (WCPO) with ethanol in the presence of calcium oxide impregnated palm shell activated carbon (CaO/PSAC) solid catalyst was investigated. This work was determined the optimum conditions for the production of ethyl ester from PS and WCPO in order to obtain fatty acid ethyl ester (FAEE) with the highest yield. The effects of reaction variables such as residence time, ethanol/oil molar ratio, reaction temperature, catalyst bed height and reusability of catalyst in a reactor system on the yield of biodiesel were considered. The optimum conditions were the residence time 2-3 h, ethanol/oil molar ratio 16-20, reaction temperature at 800C, and catalyst bed height 300 mm which yielded 89.46% and 83.32% of the PS and WCPO conversion, respectively. CaO/PSAC could be used repeatedly for 4 times without any activation treatment and no obvious activity loss was observed. It has potential for industrial application in the transesterification of triglyceride (TG). The fuel properties of biodiesel were determined.